Frequency of the anti-glutamic acid decarboxylase immunological marker in patients with diabetes duration longer than three years in southern Brazil - Moreira, Marina Carolina; Lara, Gustavo Müller; Linden, Rafael; Feksa, Luciane Rosa; Tavares, Rejane Giacomelli; Almeida, Sabrina Esteves de Matos; Berlese, Daiane Bolzan (São Paulo Medical Journal, 2011)
CONTEXT AND OBJECTIVE: The anti-GAD (glutamic acid decarboxylase) antibody is considered to be an important marker for type 1 diabetes mellitus (DM1), with frequency that varies depending on the population studied and the duration of the disease. Therefore, the aim of this study was to determine the frequency of this autoantibody in a group of patients in southern Brazil with DM1 that had been diagnosed more than three years previously. DESIGN AND SETTING: Analytical cross-sectional study with a control group conducted at the Biomedicine Laboratory of Universidade Feevale. METHODS: This study was conducted between June 2007 and December 2008, and 109 individuals were enrolled during this period. Fifty-eight were DM1 patients and 51 were individuals free from DM1 and without any history of diabetes, who constituted the control group. RESULTS: In the DM1 group, the mean age was 27 ± 1.7 years and 50% were men. The mean fasting blood glucose in the DM1 group was 208 ± 15 mg/dl and mean HbA1c (glycosylated hemoglobin) was 8.7 ± 0.25%. In the control group, the mean fasting blood glucose and HbA1c were 82 mg/dl and 5.0% respectively. Thirty-seven individuals with DM1 (63.8%) were positive for anti-GAD, and this proportion was significantly larger than in the control group. CONCLUSIONS: These results show the high prevalence of anti-GAD in the population of diabetic patients in southern Brazil, thus indicating that the antibody was still present a long time after the disease had been diagnosed.